Hall technique for the treatment of hypomineralized second primary molars: case report - Patricia Bittencourt Santos; Eloisa Fernandes; Maria Conceição Solano (Revista de Odontopediatria Latinoamericana)
Introduction: Hypomineralized second primary molar (HSPM) is an enamel defect that affects 1 to 4 second primary molars. Aim: To describe the use of the Hall Technique (HT) in rehabilitating a severely affected second primary molar in patient with HSPM and emphasize the importance of clinical monitoring in the management of fractures and caries lesions. Case report: 9-year-old boy presented esthetic issues and painful, sensitive teeth. Molar incisor hypomineralization (MIH) and HSPM were diagnozed. Preventive treatment was performed, followed by dental restoration using the HT. Recall visits were scheduled every 3 months. A recall appointment after 12 months revealed a stable treatment. His teeth were free from caries and no fracture was observed. Discussion: HT is a favorable restorative option for HSPM involving two or more surfaces. Conclusion: HT may be considered a feasible alternative to restore HSPM teeth.